2013
DOI: 10.1007/s00508-013-0431-2
|View full text |Cite|
|
Sign up to set email alerts
|

Differences in the metabolic status of healthy adults with and without active brown adipose tissue

Abstract: The healthy adults with active BAT in an un-stimulated state had favorable metabolic profiles suggesting that active BAT may be a potential target for preventing and treating obesity and other metabolic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 30 publications
4
26
0
Order By: Relevance
“…Moreover, recent studies on the effects of BAT transplantation in mice have indicated possible roles of BAT in the regulation of glucose and lipid metabolism through some body fat-independent mechanisms [12,13]. A significant independent impact of BAT on blood glucose and hemoglobin A1c was also shown in humans [58,59]. These findings collectively suggest that BAT may also be involved in the etiology of glucose intolerance, independently of and/or secondly to obesity.…”
Section: Perspectivesmentioning
confidence: 86%
“…Moreover, recent studies on the effects of BAT transplantation in mice have indicated possible roles of BAT in the regulation of glucose and lipid metabolism through some body fat-independent mechanisms [12,13]. A significant independent impact of BAT on blood glucose and hemoglobin A1c was also shown in humans [58,59]. These findings collectively suggest that BAT may also be involved in the etiology of glucose intolerance, independently of and/or secondly to obesity.…”
Section: Perspectivesmentioning
confidence: 86%
“…However, although ABAT has been shown to play an important role in the clearance of plasma lipids and to effectively treat hyperlipidaemia in animal studies, no study including an appropriate control group has yet been performed in humans [6,7]. Therefore, we here investigated the relationship between the presence of ABAT and blood lipid profiles, liver function, and NAFLD prevalence in patients undergoing 18 F-FDG PET/CT examinations for suspicion or staging of a malignancy.…”
Section: Introductionmentioning
confidence: 91%
“…As the outdoor temperature is related to 18 F-FDG uptake in ABAT [9], the outdoor temperatures in Istanbul for the dates of the scans were obtained from the Regional Meteorological Centre. Taking into consideration the regional outdoor temperatures and patient age, sex, fasting plasma glucose level, and BMI, each ABAT(+) patient was enrolled together with three matched ABAT(−) patients.…”
Section: Study Patientsmentioning
confidence: 99%
See 2 more Smart Citations